Relationship between variability of the semidiurnal tide in the Northern Hemisphere mesosphere and quasi-stationary planetary waves throughout the global middle atmosphere - X. Xu; A. H. Manson; C. E. Meek; T. Chshyolkova; J. R. Drummond; C. M. Hall; Ch. Jacobi; D. Riggin; R. E. Hibbins; M. Tsutsumi; W. K. Hocking; W. E. Ward (Annales Geophysicae, 2009)
To investigate possible couplings between planetary waves and the semidiurnal tide (SDT), this work examines the statistical correlations between the SDT amplitudes observed in the Northern Hemisphere (NH) mesosphere and stationary planetary wave (SPW) with wavenumber S=1 (SPW1) amplitudes throughout the global stratosphere and mesosphere. The latter are derived from the Aura-MLS temperature measurements. During NH summer-fall (July–October), the mesospheric SDT amplitudes observed at Svalbard (78° N) and Eureka (80° N) usually do not show persistent correlations with the SPW1 amplitudes in the opposite hemisphere. Although the SDT amplitudes observed at lower latitudes (~50–70° N), especially at Saskatoon (52° N), are often shown to be highly and positively correlated with the SPW1 amplitudes in high southern latitudes, these correlations cannot be sufficiently explained as evidence for a direct physical link between the Southern Hemisphere (SH) winter-early spring SPW and NH summer-early fall mesospheric SDT. This is because the migrating tide's contribution is usually dominant in the mid-high latitude (~50–70° N) NH mesosphere during the local late summer-early fall (July–September). The numerical correlation is dominated by similar low-frequency variability or trends between the amplitudes of the NH SDT and SH SPW1 during the respective equinoctial transitions. In contradistinction, during NH winter (November–February), the mesospheric SDT amplitudes at northern mid-high latitudes (~50–80° N) are observed to be significantly and positively correlated with the SPW1 amplitudes in the same hemisphere in most cases. Because both the SPW and migrating SDT are large in the NH during the local winter, a non-linear interaction between SPW and migrating SDT probably occurs, thus providing a global non-migrating SDT. This is consistent with observations of SDT in Antarctica that are large in summer than in winter. It is suggested that climatological hemispheric asymmetry, e.g. the SH and NH winter characteristics are ...